Recent advance of in vitro models in natural phytochemicals absorption and metabolism. Issue 6 (23rd March 2022) - Huang, Yajun; Chen, Yaobin; Lu, Suyue; Zhao, Chao
Abstract : Natural phytochemicals absorption and metabolic process are mainly in the human gut. Simulating the absorption and metabolism of natural phytochemicals in vitro to predict the rate and degree of absorption of natural phytochemicals provides convenience for many researchers. However, in this process, many physiological factors in vitro are affected, such as stomach and intestinal juice composition, pH, intestinal transmission rate and so on. In recent years, the research methods have gradually improved to make these models more suitable for the natural phytochemicals absorption process, in vitro simulation models have become an essential means to study natural phytochemicals absorption. Therefore, this paper introduces the advantages and disadvantages of commonly used in vitro simulation models of natural phytochemicals absorption and metabolism, as well as briefly introduces the working principle of each model. To provide a theoretical basis for simulating natural phytochemicals absorption in vitro and development and utilization of natural phytochemicals.